Long Noncoding RNA LINC01134 Promotes Hepatocellular Carcinoma Metastasis via Activating AKT1S1 and NF-κB Signaling - Wang, Chao; Chen, Yan; Chen, Kunlun; Zhang, Lei (Frontiers in Cell and Developmental Biology, 2020)
Hepatocellular carcinoma is one of the most common malignancies with poor outcomes. The main cause of HCC-related deaths are recurrence and metastasis. Long noncoding RNAs (lncRNAs) are recently identified as critical regulators in cancers. However, the lncRNAs involved in HCC recurrence and metastasis are poorly understand. In this study, via analyzing the Cancer Genome Atlas (TCGA) Liver Hepatocellular Carcinoma (LIHC) dataset, we identified a novel lncRNA LINC01134, which is highly expressed in HCC tissues and correlated with microvascular invasion, macrovascular invasion, recurrence, and poor overall survival of HCC patients. Functional experiments revealed that ectopic expression of LINC01134 promotes HCC cell migration and invasion in vitro, and HCC liver metastasis and lung metastasis in vivo. Knockdown of LINC01134 represses HCC cell migration and invasion in vitro, and HCC liver metastasis and lung metastasis in vivo. Mechanistically, we found that LINC01134 directly binds the promoter of AKT1S1 and activates AKT1S1 expression. Via activating AKT1S1, LINC01134 further activates NF-κB signaling. The expression of LINC01134 is significantly positively correlated with that of AKT1S1 in HCC tissues. In line with LINC01134, AKT1S1 is also highly expressed in HCC tissues and correlated with poor survival of HCC patients. Functional rescue experiments showed that repressing AKT1S1 or NF-κB signaling both abrogate the roles of LINC01134 in HCC. Taken together, these findings recognized LINC01134 as a novel oncogenic lncRNA, which indicates vascular invasion, recurrence, and poor overall survival of HCC patients. LINC01134 promotes HCC metastasis via activating AKT1S1 expression and subsequently activating NF-κB signaling. This study suggested LINC01134 as a potential prognostic biomarker and therapeutic target for HCC.